Identification of glutamine as a potential therapeutic target in dry eye disease - Xiaoniao Chen; Chuyue Zhang; Fei Peng; Lingling Wu; Deyi Zhuo; Liqiang Wang; Min Zhang; Zhaohui Li; Lei Tian; Ying Jie; Yifei Huang; Xinji Yang; et al. (Signal Transduction and Targeted Therapy)
Abstract Dry eye disease (DED) is a prevalent inflammatory condition significantly impacting quality of life, yet lacks effective pharmacological therapies. Herein, we proposed a novel approach to modulate the inflammation through metabolic remodeling, thus promoting dry eye recovery. Our study demonstrated that co-treatment with mesenchymal stem cells (MSCs) and thymosin beta-4 (Tβ4) yielded the best therapeutic outcome against dry eye, surpassing monotherapy outcomes. In situ metabolomics through matrix-assisted laser desorption/ionization mass spectrometry imaging (MALDI-MSI) revealed increased glutamine levels in cornea following MSC + Tβ4 combined therapy. Inhibition of glutamine reversed the anti-inflammatory, anti-apoptotic, and homeostasis-preserving effects observed with combined therapy, highlighting the critical role of glutamine in dry eye therapy. Clinical cases and rodent model showed elevated expression of glutaminase (GLS1), an upstream enzyme in glutamine metabolism, following dry eye injury. Mechanistic studies indicated that overexpression and inhibition of GLS1 counteracted and enhanced, respectively, the anti-inflammatory effects of combined therapy, underscoring GLS1’s pivotal role in regulating glutamine metabolism. Furthermore, single-cell sequencing revealed a distinct subset of pro-inflammatory and pro-fibrotic corneal epithelial cells in the dry eye model, while glutamine treatment downregulated those subclusters, thereby reducing their inflammatory cytokine secretion. In summary, glutamine effectively ameliorated inflammation and the occurrence of apoptosis by downregulating the pro-inflammatory and pro-fibrotic corneal epithelial cells subclusters and the related IκBα/NF-κB signaling. The present study suggests that glutamine metabolism plays a critical, previously unrecognized role in DED and proposes an attractive strategy to enhance glutamine metabolism by inhibiting the enzyme GLS1 and thus alleviating inflammation-driven DED progression.